Peran Katekis Dalam Meningkatkan Keterlibatan Dan Partisipasi Generasi Muda Pada Pemilu Tahun 2024 - Adrian Yanuar Prameswara; Intansakti Pius X (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Elections are the key to democracy. Young people are expected to have an awareness of their responsibilities as citizens by being willing to be involved in preparations until the implementation of the elections later. Given that the 2024 election is dominated by young people as the most voters. The Church also paid attention to the situation. In its work the church is assisted by Catechists in their service to the people. This study aims to determine the role of catechists in increasing the involvement and participation of the younger generation in the 2024 elections. The method used in this study is a literature review. The results of this study show that catechists have a role as political educators for young people, and catechesis of people is a means of accommodating the aspirations, ideas, and ideas of young people, then catechists are also reformers of paradigms about church and state.